Adverse Perinatal Outcomes Associated with Increasing Maternal Obesity - Addicott, Katherine; Nudelman, Matthew; Putty, Krista; Prasher, Priya; Preston, Deborah; Yoost, Jennie L; DeFruscio, Annie; Bartlett, David; Cavender, Catherine; Carter, Meagen; Datz, Hannah; Rodriquez, Kayla; Werthammer, Joseph (American Journal of Perinatology, 2023)
Objective The aim of this study was to determine adverse perinatal outcomes related to maternal preconception body mass index (BMI).Study Design This is a retrospective observational cohort study at a single institution of 500 consecutive mothers of normal weight with a preconception BMI of 18.5 to less than 25 and 500 additional obese mothers with a preconception BMI more than or equal to 30. Maternal/newborn metrics were stratified by maternal preconception BMI and trend analysis was performed both by simple univariable and multivariable logistic regression analysis.Results The study included 858 mother/baby dyads after 142 were excluded. Trend analysis demonstrated higher preconception BMI was significantly associated with progressively higher rates of cesarean section (p < 0.001), preeclampsia p < 0.001), gestational diabetes (p < 0.001), preterm birth (p = 0.001), lower 1- and 5 minutes Apgar scores (p < 0.001), and neonatal intensive care unit admission (p = 0.002). These associations remained significant in both simple univariable and multivariable logistic regression models.Conclusion We demonstrated obese women are more likely to have maternal complications and neonatal morbidity when compared with normal weight mothers. Maternal and fetal complications increase with increasing obesity with superobese mothers (BMI ≥ 50) having more perinatal adverse outcomes when compared with other classes of obesity. It is reasonable to counsel weight loss prior to conception of women with BMI more than or equal to 30 in an effort to reduce maternal complications and neonatal morbidity related to pregnancy.Key Points
Keywords: maternal obesity; adverse perinatal outcomes; superobesity